Effect of Wood Extractives on the Equilibrium Moisture Content of Six Sudanese Hardwood Species - Ahmed, Zeinab A. A.; Abdelgadir, Abdelazim Yassin; Abdalla, Ashraf Mohameed Ahmed (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this investigation was to study the effect of extractive content on the wood sorption isotherms of six Sudanese hardwood species i.e. Acacia nilotica, A.senegal, Anogeissus leiocarpus, Boswellia papyrifera, Ailanthus excelsa and Calotropis procera growing in North and South Kordofan States. For each species, wood samples were collected from six trees, from which specimens were prepared. The effect of extractives on equilibrium moisture content was studied by comparing the equilibrium moisture content of hot water extracted and unextracted wood. Experimental equilibrium moisture content values for extracted and unextracted specimens were obtained at different levels of relative humidity. These specimens were placed in a closed desiccator, which contained saturated salt solution or different concentrations of sulphuric acid to maintain relative humidity and then kept in an oven at the specified temperature (60 ○ C) until equilibrium moisture content was obtained. Desorption and adsorption isotherms of the six wood species exhibited sigmoid curves. The results showed direct relationship between equilibrium moisture content and relative humidity that could be well explained by third-order polynomial functions. The effect of extraction was significant at few relative humidity values in some species; unextracted wood had higher equilibrium moisture content than extracted wood.